Natural drying of forest biomass: Effect of stack height and cover in the province of Valdivia, Chile - Labbé, Rodrigo; Carey, Patricio; Trincado, Guillermo; Thiers, Oscar (BOSQUE, 2018)
Moisture content is considered one of the most important quality parameters in wood fuels. In this context, natural drying is a cheap and easy method to reach adequate moisture content in forest biomass. The objective of this study is to evaluate the effect of different treatments feasible to be applied operationally in the natural drying of whole small trees. Whole trees from natural regeneration of Acacia melanoxylon with diameters of 3 to 12 cm were used in this research, in Los Ríos Region, Chile. Trees were stacked into piles outside the forest between January and December 2012, distributed in 12 biomass piles. Piles were evaluated at two heights (one and two meters), and two protection levels (without protection and using a semi-permeable cover). A factorial design with three repetitions per treatment was used. Indirect measurements of moisture content were obtained by monthly weight records. These were used to model the progress of drying in each pile. The overall effect of treatments was evaluated with factorial variance analysis using the GLM procedure. For the study conditions, results indicate that natural biomass drying has a strong seasonal component. Consequently the use of cover was essential in winter season. During summer months the cover was not necessary, being able to reach moisture content lower than 30 % after the summer if storage started in the beginning of January. In this case, better results were obtained with the two-meter-high piles because they were less sensitive to occasional summer rains.